SGA to work with UUM on golf devt: He (coach) can also come and conduct coaching clinics/courses for our players and teachers...we need to have more coaches in schools so that we can do development. - Alias, Shahary (Borneo Post (kk), 2013)
KUCHING: Sarawak Golf Association (SGA) is looking forward to working closely with Kedah's Universiti Utara Malaysia (UUM) to boost development of golf locally."They (UUM) canalso send their Australian pro coach to Sarawak to help us conduct two week courses and do school and junior programmes," SGA's secretary Shahary Alias said recently.